Legal Regulation of Ensuring Nuclear Safety and Security in Ukraine on the Way to European Integration - Dubchak, Sergiy; Goshovska, Valentyna; Goshovskyi, Volodymyr; Svetlychny, Oleksandr; Gulac, Olena (European Journal of Sustainable Development, 2020)
The article is devoted to the analysis of legal regulation of the sphere of nuclear safety and security of Ukraine on the way to European integration. The authors drew attention to the importance of Ukraine achieving the necessary level of and nuclear sefaty and security adopted in the EU member states. The emphasis was placed on the fact that the prospects for fulfilling national obligations in the field of nuclear safety in accordance with European standards directly depend on solving the problems of ensuring the functioning of nuclear facilities, the physical protection of nuclear materials and installations as well as radioactive waste management. The main directions of ensuring the nuclear safety and secutiry in the world within the international law are considered. The role and activities of the International Atomic Energy Agency (IAEA) in setting up a regulatory framework for nuclear safety and security are analyzed. The international legal framework for nuclear safety and security was discused.The legislative basis for nuclear safety and secutiry in the EU IS characterized. The issue of legal norms unification in the field of nuclear safety regulation of EU member states was considered. The principles of legal regulation of nuclear a safety and security in Ukraine are characterized. Key words: nuclear safety, nuclear security, public administration of nuclear safety and security, legal regulation of nuclear safety and security, European integration, sustainable development in the field of ensuring nuclear safety and security. UDC 35:574:339.9:349.6 JEL Classification: K 23, K 32, K 33, Q 5